Predicting Concussion Recovery with PHQ-9 and GAD-7. Issue 12 (December 2021) - Narducci, Dusty Marie; Moran, Byron; Coris, Eric; Tsalatsanis, Athanasios; Graulich, Ian; Del Rossi, Gianluca
Abstract : This retrospective cohort study sought to determine whether scores obtained from the Patient Health Questionnaire-9 or the General Anxiety Disorder-7 instruments administered following a concussion can be used to predict a subject's recovery time or likelihood of recovery. A total of 502 concussed subjects completed a Patient Health Questionnaire-9 or General Anxiety Disorder-7 during their initial visit and all subsequent visits during the recovery period (ie, at 14, 28, 56, and 84 days). Supplemental digital content is available in the text. Abstract: Objective: To determine whether scores obtained from Patient Health Questionnaire-9 (PHQ-9) or the General Anxiety Disorder-7 (GAD-7) instruments administered following a concussion can be used to predict recovery time. Method: Retrospective cohort study in a university-based specialty concussion center of 502 concussed participants. Participants completed a PHQ-9 and GAD-7 during their initial visit and subsequent visits during the recovery period (ie, at 14, 28, 56, and 84 days). Results: The median recovery time from a concussion was 21 days from the initial clinical evaluation; however, individuals with a PHQ-9 score ≤ 6 (n = 262) had a median recovery time of 17 (95% confidence interval [CI] 15–19) days, whereas those with PHQ-9 scores >6 (n = 240) had a median recovery time of 33 (95% CI 28–37) days and a hazard ratio of 0.525 (95% CI 0.438–0.629, P < 0.0001). For individuals with a GAD-7 score ≤ 4 (n = 259), the median recovery was 19 (95% CI 17–21), days whereas for those with a GAD-7 score > 4 (n = 243), the median recovery was 32 (95% CI 28–36) days with a hazard ratio of 0.554 (95% CI 0.462–0.664, P < 0.00). Conclusions: Scores obtained from PHQ-9 and GAD-7 screening tools appear to be predictive of an individual's recovery and may help identify those subjects who may benefit from early psychological interventions.